Kearifan Lokal Sebagai Implementasi P5 Pada Kurikulum Merdeka Di SMA Pembangunan Laboratorium UNP - Aisyah Rahmadani; Hafizah Zarga Anggrayni; Nabila Muthia Rezky Maghfirah; Nashiro Jamila (Populer: Jurnal Penelitian Mahasiswa, 2024)
This research discusses the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) in the Independent Curriculum at the UNP Laboratory Development High School. The Merdeka Curriculum emphasizes the character of students with six main dimensions, such as faith, diversity, mutual cooperation, independence, critical thinking and creativity. Implementation of P5 is carried out through project-based activities involving these elements, with a focus on the theme "Local Wisdom." UNP Laboratory Development High School implements P5 every three months, involving all education stakeholders. P5 evaluation does not focus on written grades, but rather on strengthening character, especially local wisdom which describes the culture, identity and ethics of the local community. This program aims to prepare students to face the challenges of globalization while maintaining harmony with Pancasila values ​​and local wisdom. The research method used was qualitative with data collection through observation and interviews with the P5 coordinating teacher. The findings show that P5 involves project-based activities aimed at strengthening students' competencies and character in accordance with the Pancasila Student Profile. The implication of this research is the importance of character education that integrates local wisdom in learning to create a competent and characterful generation.